Obesity-induces Organ and Tissue Specific Tight Junction Restructuring and Barrier Deregulation by Claudin Switching - Rizwan Ahmad (Nature Portfolio, 2017)
Abstract Obesity increases susceptibility to multiple organ disorders, however, underlying mechanisms remain unclear. The subclinical inflammation assisted by obesity-induced gut permeability may underlie obesity-associated co-morbidities. Despite eminent clinical significance of the obesity led gut barrier abnormalities, its precise molecular regulation remains unclear. It is also unknown whether barrier deregulations, similar to the gut, characterize other vital organs in obese individuals. The claudin family of proteins is integral to the tight junction (TJ), the apical cell-cell adhesion and a key regulator of the epithelial barrier. Using comprehensive physiological and biochemical analysis of intestinal and renal tissues from high-fat diet fed mice, critical for maintaining metabolic homeostasis, this study demonstrates that profound TJ-restructuring by organ and tissue-specific claudin switching characterize obese organs. Protein expression and cellular distribution were examined. In-silico analysis further highlighted potential association of select claudins, modulated by the obesity, with signaling and metabolic pathways of pathological significance. In vitro studies using Leptin or DCA-treatment suggested causal significance of obesity-induced changes in tissue microenvironment in regulating barrier deregulations in tissue-specific manner. Overall, current findings advances our understanding of the molecular undertakings of obesity associated changes that help predispose to specific diseases and also identifies novel windows of preventive and/or therapeutic interventions.